PELANGGARAN KETERBUKAAN (DISCLOSURE) TERHADAP EMITEN DI PASAR MODAL - Fachruddin Razi (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
This paper discusses about the problem of disclosure in capital market and the sanction of infraction. The result shows that the investor is requested to be more careful and in-depth into capital market analysis, a good and adequate transparency from the issuers, and also responsibility from institution or other support profession toward losses suffered by investor due to incorrect and misleading information. Sanction can be given by Bapepam as one way of completion through administration or civil law before taking legal action, besides doing its function to fulfill principle “disclosure” adequate.Keywords    : Disclosure, Transparency, Capital Market